PENERAPAN TEKNOLOGI ALAT SPINNER PADA PRODUK OLAHAN KERIPIK UMKM SWAKARYA DI DESA RULUNG SARI, LAMPUNG SELATAN - Herry Wardono; Simparmin Br Ginting; Herti Utami (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2022)
The group of UMKM Swakarya, located in Desa Rulung Sari, Lampung Selatan is a home industry that produce variety of processed chips. This Swakarsa group is one of the UMKM that was initiated in 2020. At that time, the sluggish economy occurred, due to the Covid 19 pandemic, so the idea arose to sell processed products, namely banana chips and cassava chips. The problem with this partner of Swakarya UMKM is that the chip product turns out to be not hard like chips in general because the product does not drain the oil perfectly with a drainer, so the product cannot be stored longer. The Unila team provides solutions by using appropriate technology tools in order to drain the oil. In the manufacture of this chip product, after being fried, a spinner is used to drain the oil so that the chip product has a little oil content and is ready to be packaged and marketed. By providing this spinner, a tool for draining oil, it is expected that it will increase the production capacity of chips and the quality of chips produced by the partner for the better.